2014
DOI: 10.4012/dmj.2013-344
|View full text |Cite
|
Sign up to set email alerts
|

Influence of abutment model materials on the fracture loads of three-unit fixed dental prostheses

Abstract: This study evaluated and compared the influence of different supporting abutment models on the fracture loads of three-unit fixed dental prostheses (FDPs) fabricated from the following materials (n=24/material): (i) IPS e.max CAD-on, (ii) IPS e.max ZirCAD, and (iii) Telio CAD. Twelve FDPs of each group were adhesively cemented on a polymeric model and on a base metal alloy one. For the fracture load test the FDPs were loaded at the centre of the pontic (1 mm/min). The data were analyzed using descriptive stati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 23 publications
(40 reference statements)
1
19
0
Order By: Relevance
“…Herein, the loading stainless steel ball was able to fit in a cavity formed in the middle of the pontic, and a three-point contact between the occlusal surface and steel ball was achieved successfully. 17 Clinically, the mechanical failure of dental prostheses occurs a long time after their application, indicating that fatigue failure accounts for a larger proportion of the failure cases than acute overload. 20 Damage is accumulated by repetitive contact between maxillary and mandibular teeth, and the lifetime and survival rate of the prosthesis are reduced.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Herein, the loading stainless steel ball was able to fit in a cavity formed in the middle of the pontic, and a three-point contact between the occlusal surface and steel ball was achieved successfully. 17 Clinically, the mechanical failure of dental prostheses occurs a long time after their application, indicating that fatigue failure accounts for a larger proportion of the failure cases than acute overload. 20 Damage is accumulated by repetitive contact between maxillary and mandibular teeth, and the lifetime and survival rate of the prosthesis are reduced.…”
Section: Discussionmentioning
confidence: 99%
“…The connectors included mesiodistal cross-sectional areas of 31.3 mm 2 , a buccolingual width of 5.7 mm, and an occlusogingival height of 7 mm. 17 …”
Section: Methodsmentioning
confidence: 99%
“…Wimmer and colleagues found that fracture resistance of zirconia FDPs was increased by 30% when the FDPs were attached to base metal abutment teeth, in contrast with polymer abutment teeth, and axially loaded on the pontic. 41 In such a test, the extent of bending of the FDP is restricted by the abutment teeth, resulting in less strain (and therefore stress) on the basal side of the connectors when a given load is applied, thus leading to higher fracture resistance. In contrast, in our study oblique loading was used, leading to high stress in the adhesively attached retainer walls also.…”
Section: Discussionmentioning
confidence: 99%
“… 19 20 21 22 Press-over technique and CAD-on technology are two new veneering methods which have shown higher mechanical properties compared to conventional layering technique. 19 20 21 22 In press-over technique after application of a special liner to the zirconia framework, the veneer is waxed upon it. Alternatively, the wax or resin replica of the veneer could be produced by CAD/CAM technology, connected to the framework and invested using fluorapatiteglass-ceramic ingots.…”
Section: Introductionmentioning
confidence: 99%